Characteristics of prescription opioid abusers in treatment: Prescription opioid use history, age, use patterns, and functional severity - Butler, PhD, Stephen F.; Black, PhD, Ryan A.; Grimes Serrano, PhD, Jill M.; Wood, MPH, Mollie E.; Budman, PhD, Simon H. (Journal of Opioid Management, 2018)
Research has raised the possibility that the length of time one engages in nonmedical use of prescription opioids may be associated with abuse of other drugs, more risky drug-related behavior, and more severe functional problems. This study drew on data from the Addiction Severity Index-Multimedia Version® Connect system. A total of 55,341 client assessments at substance abuse treatment centers were analyzed to help understand the impact of length of time one has abused opioids on the patterns of abuse and functional problems. From this larger sample, 5,686 individuals who had abused a prescription opioid within the past 30 days were studied. Multiple logistic regression analyses were run to examine the impact of length of time abusing any opioid, after adjusting for several demographic variables, on route of administration (injection or injection/snorting), other drugs abused, and functioning in the areas of medical status, employment, drug and alcohol use, legal status, family and social problems, and psychiatric status. Overall findings supported the hypothesis that length of opioid abuse is associated with higher risk of drug use patterns as well as functional problems.